If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -14 = 7x + 7 Reorder the terms: -14 + 3x = 7x + 7 Reorder the terms: -14 + 3x = 7 + 7x Solving -14 + 3x = 7 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -14 + 3x + -7x = 7 + 7x + -7x Combine like terms: 3x + -7x = -4x -14 + -4x = 7 + 7x + -7x Combine like terms: 7x + -7x = 0 -14 + -4x = 7 + 0 -14 + -4x = 7 Add '14' to each side of the equation. -14 + 14 + -4x = 7 + 14 Combine like terms: -14 + 14 = 0 0 + -4x = 7 + 14 -4x = 7 + 14 Combine like terms: 7 + 14 = 21 -4x = 21 Divide each side by '-4'. x = -5.25 Simplifying x = -5.25
| 4y-1+y+31=6y+30-4y | | 4+55x=44x+7 | | -r+24=-4(r-6) | | -9(b-3)+3b= | | 27=a-18 | | -28=4x-2(3x+6) | | (5y+4)(5y-4)=0 | | 3(z-2)+6x-2= | | 5n+11=32 | | 10-2x=x-8 | | .07(5t-3)=.35(t+5)-1.96 | | 5d+4d+3d-4=2d | | 4(9p+6)+3p= | | 4x^2+17x+2ifx=10 | | 6x+1=18x-29 | | 3(6+x)=54 | | 4c+2c+5c=11c | | 5(7-2a)= | | -6(-5n+4)=38-n | | -5(5p+4)-30=2(3p+6) | | (8+y)(3+y)=0 | | .4(a+20)=6 | | 3x-4(3x+3)=60 | | 3(3-5x)= | | 3x(4x+40)=360 | | x^2*x^4=15625 | | 62=-2(-1-2t) | | (8c^4-1)(2c^4-4)= | | 5x=-2-13 | | 34p=45p+32 | | 6(v-4)-2=-7(-4v+2)-4v | | 7x+40=360 |